A Systematic Review of Video Modeling Interventions to Improve the Independent Living Skills of Students with Autism Spectrum Disorder and Intellectual Disability - Wynkoop, Kaylee S.; Wissinger, Daniel R.; Horn, Matthew Van (Journal of the American Academy of Special Education Professionals, 2019)
The purpose of this meta-analysis is to review the single-subject experimental literature and aggregate results across studies investigating the effects of video modeling (VM) to address independent living skill deficits of students with autism spectrum disorder (ASD) and intellectual disability (ID). A total of 20 studies including 67 participants with ASD and/or ID met inclusion criteria. We extracted data from included studies and evaluated each using visual analysis and by calculating the average weighted percentage of non-overlapping data (PND) and confidence intervals (CI). Finally, we stratified results by VM approach and examined moderator variables to determine overall effect sizes, which VM approach appeared to be most effective, and whether specific study-level characteristics moderated the effects of the VM intervention. Results indicated that, overall, VM was an effective treatment for improving independent living skills of students with ASD and/or ID, however, our calculated effect size was somewhat lower than those seen in previous reviews of the VM literature. We found that VM with prompting was most likely to be effective and that study quality and student age likely mediated the effects of VM interventions whereas study setting and disability likely did not. Comparisons between our results and results of similar previously conducted meta-analyses are discussed, implications for practice are reviewed, and directions for future research are recommended.